1974
DOI: 10.1104/pp.54.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 0.03% Carbon Dioxide on Protein Metabolism of Etiolated Avena sativa Coleoptiles

Abstract: The influence of indoleacetic acid, 0.03 % C02, and malate on protein metabolism of etiolated Avena sativa coleoptile sections has been investigated. All three were found to elevate both the rate of incorporation of labeled leucine into protein, and the level of soluble protein. The synergistic relationship between IAA and 0.03% CO2 in stimulating the growth of etiolated Avena coleoptile sections has been previously described (1), and the involvement of protein synthesis in auxin-stimulated growth is well docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1974
1974
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Hart and Berrie (7) found that 3% CO2 in the atmosphere abolishes the inhibition of A. fatua seed germination by light. The growth of various types of excised plant tissues-roots (18,19), carrot disks (18), and Avena coleoptiles (1), is promoted by supplementing the medium with bicarbonate or a suitable acid. Johnson and Rayle (11) found that fusicoccin and IAA promote dark fixation in Avena coleoptiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hart and Berrie (7) found that 3% CO2 in the atmosphere abolishes the inhibition of A. fatua seed germination by light. The growth of various types of excised plant tissues-roots (18,19), carrot disks (18), and Avena coleoptiles (1), is promoted by supplementing the medium with bicarbonate or a suitable acid. Johnson and Rayle (11) found that fusicoccin and IAA promote dark fixation in Avena coleoptiles.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations were made on the promotion of growth of excised plant tissues by the supply of bicarbonate or, alternatively, a suitable tricarboxylic acid cycle acid in the growth medium (1,18,19). Bacterial mutants lacking PEP2 carboxylase also require malate for growth (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide has been known to stimulate growth of various kinds of plant tissues and organs; for example, eoleoptiles (Evans, 1974), hypocotyls (Goto & Esashi, 1974) and seed tissues (Esashi & Katoh, 1975). Evans, Ray & Reinhold (1971) suggested that the stimulation of elongation by CO2 is an acid effect, and some others (Bown & Aung, 1974;Haschke & Luttge, 1977) reported that CO2 fixation may be involved in C02-stimulated elongation. In Table 2, the elongation-stimulating effects of CO2 were accompanied by increases in dry weight of the eoleoptiles and these effects required O2 at concentrations above 0.08 m-' m"^ (Fig.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Splittstoesser (14) proposed that growth stimulation of etiolated plant tissues by atmospheric CO2 involved dark CO2 fixation and the consequent synthesis of 4 This reaction is essentially irreversible, and in vivo oxaloacetate is readily converted to malate and aspartate. In addition, the enzyme has a high affinity for CO2 which allows it to fix CO2 at concentrations less than 0.03% (12).…”
Section: Resultsmentioning
confidence: 99%